Impact of Parental Encouragement on Level of Aspiration and Academic Performance: A Comparative Study on Adolescents of Uttarakhand - Rai, Geeta (INDIAN EDUCATIONAL REVIEW, 2014)
The present study entitled ‘Impact of Parental Encouragement on Level of Aspiration and Academic Performance: A Comparative Study on Adolescents of Uttarakhand’, was carried out in secondary and higher secondary schools of Uttarakhand. It was an attempt to determine the effect of Parental Encouragement on Level of Aspiration and Academic Performance of adolescents. A total of 800 respondents were sampled based on random sampling technique. The data was collected by using Parental Encouragement Scale and Aspiration Scale. Academic Performance was measured on the basis of the marks obtained in Class X and data was analysed using suitable statistical methods. Results indicated that majority of students received average amount of parental encouragement. When groups differentiated on the basis of parental encouragement was analysed on level of aspiration, it was found that they differed on Number of Times the Goal Reach Score (NTRS) but no significant differences were found on other two scores i.e. Goal Discrepancy Score (GDS) and Attainment Discrepancy Score (ADS). Hence, the null hypotheses stating that ‘students differentiated on the basis of parental encouragement (high, average, low) would not differ significantly on all dimensions of level of aspiration was partially accepted. Further, no significant difference was found between the groups on academic performance. The present study has a lot of significance for parents and adolescents as it deals with the important aspects of adolescent’s developmental variables like aspiration and academic performance which is determined by the parental encouragement provided to them.